Response of Several Melon Varieties (Cucumis melo L.) Effect of EM4 Application - Palandro, Nadhea; Saptadi, Darmawan; Purnamaningsih, Sri Lestari (Produksi Tanaman, 2023)
Melon is one of the horticultural crops that has the potential to be developed and can meet the nutritional needs of families. The main problem faced by melon farmers is that the demand for melons cannot be fulfilled as a result of the low quality of the melons and the melon seeds are still imported. The use of hybrid varieties is indispensable in increasing market competitiveness nationally and internationally. The aim of the research was to study the interaction of melon varieties with EM4 applications. The materials used in this research activity were the seeds of the Glamor variety, Gracia variety, Action 434 variety, polybags, raffia rope, tissue, name tags, soil, compost, rice husk charcoal, EM4, NPK fertilizer, and KNO3 fertilizer. This study was a factorial experiment which was arranged using a Randomized Block Design (RBD). The first factor is the application of EM4 with 3 levels. The second factor is the use of varieties with 3 levels, namely the Glamor, Gracia, and Action 434 varieties. This research was carried out from September 2021 to December 2021 on the rooftop of the central building of the Faculty of Agriculture, University of Brawijaya. The results showed that there was no significant interaction between the three varieties of melon plants. with the EM4 application. This indicates that the growth response of the three varieties to EM4 is the same. Varietal treatment had a significant effect on the average time of emergence of male and female flowers of melon plants. This can be caused by the varieties used are superior varieties that can increase the production of melon plants.